DEVELOPMENT OF A NEW SCALE OF BELIEFS ABOUT THE WORRY CONSEQUENCES - Prados, Jose María (Anales de Psicología / Annals of Psychology, 2007)
In the last two decades, worry has been a revisited research topic. Several theoretical models suggest the role of certain beliefs in the beginning and the maintenance of worrying process. More precisely, “positive” beliefs about worry (i.e., worrying is useful in some way, in some how) would act as trigger of the process, and “negative beliefs about worry (i.e., worrying is dangerous) would contribute to enduring it, exacer-bating the emotional experience. But a corrected analysis of this proposal requires an assessment instrument with enough psychometric guaranties. Although some scales have been developed in last years, they have many limitations. For instance: (1) inappropriate items redaction, (2) few items and participants in the construction and analysis, and (3) asymmetric proportion among items that assess positive beliefs and items that assess negative beliefs. The main purpose of this study is to develop a new scale with a bidirectional structure and with better psychometric properties that previous instruments.